2020
DOI: 10.1186/s12888-020-02769-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and clinical predictors of response to rTMS treatment in pharmacoresistant obsessive-compulsive disorder (OCD): a retrospective study

Abstract: Background: Application of repetitive transcranial magnetic stimulation (rTMS) for treating obsessive-compulsive disorder (OCD) has been promising and approved by the Food and Drug Administration in 2018, but effects differ between patients. Knowledge about clinical predictors of rTMS response may help to increase clinical efficacy but is not available so far. Methods: In a retrospective study, we investigated the efficacy of rTMS over the dorsolateral prefrontal cortex (DLPFC) or supplementary motor area (SMA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 79 publications
(118 reference statements)
4
21
0
1
Order By: Relevance
“…On the other hand, there was no significant difference in the mean percent reduction in the total score on the Y-BOCS between males and females or between on- and off-medication. These results were consistent with the previous study that showed no difference in the response rate between males and females or between on- and off-medication [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, there was no significant difference in the mean percent reduction in the total score on the Y-BOCS between males and females or between on- and off-medication. These results were consistent with the previous study that showed no difference in the response rate between males and females or between on- and off-medication [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…Hot–cold executive dysfunctions and respective pathophysiology in the prefrontal-cingular network are prominent in psychopathology other neuropsychiatric disorders as well including but not limited obsessive–compulsive disorders ( cold -deficits driven), borderline personality disorder ( hot -deficits driven), and impulse control disorders ( cold–hot deficits driven) ( Gruner and Pittenger, 2017 ; Schulze et al, 2019 ). In this line, recent NIBS studies have also shown than modulating activity of the prefrontal-cingular and relevant subcortical regions are promising for the treatment of these disorders ( Brevet-Aeby et al, 2016 ; Molavi et al, 2020a ; Rostami et al, 2020 ).…”
Section: Clinical Implications Of Hot–cold Efs For Neuropsychiatric Disordersmentioning
confidence: 98%
“…As rTMS is a focal intervention, it is not clear whether treatments targeting OCD may have an impact on comorbidities too. While open-label studies have shown that rTMS over DLPFC/SMA/DMPFC decreases anxiety and depressive symptoms, 20 sham-controlled studies have not been consistent. [21][22][23] The limited sample sizes of the individual studies might have decreased the power to find statistically significant differences.…”
Section: Introductionmentioning
confidence: 93%